2020
DOI: 10.4103/jpbs.jpbs_271_18
|View full text |Cite
|
Sign up to set email alerts
|

Water pipe smoking affects young females and males differently with some effects on immune system cells, but none for C-reactive protein, thyroid hormones, and vitamin D

Abstract: Introduction: Water pipe smoking (WPS) is a major health threat leading to higher mortality, morbidity, and incidence of many diseases, such as inflammatory, respiratory and cardiovascular diseases; and cancers. This study aimed to determine the differences in the effects of WPS on the immune system, inflammatory markers, lipids, vitamin D, and thyroid hormones in female and male WP smokers, and compared to nonsmokers of both sexes. No other studies showed the differences between female and male W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…From the known effects of smoking, including immune system alterations (Sorensen et al, 2010;Mahassni and Alajlany, 2020), direct antibacterial activity (Pavia et al, 2000) and changes in oxygen tension (Jensen et al, 1991), we can propose many hypotheses related to our findings and to the observed changes in bacterial community compositions. For non-smokers, aand bdiversities in the gut microbiota differed significantly from those of smokers.…”
Section: Discussionmentioning
confidence: 62%
“…From the known effects of smoking, including immune system alterations (Sorensen et al, 2010;Mahassni and Alajlany, 2020), direct antibacterial activity (Pavia et al, 2000) and changes in oxygen tension (Jensen et al, 1991), we can propose many hypotheses related to our findings and to the observed changes in bacterial community compositions. For non-smokers, aand bdiversities in the gut microbiota differed significantly from those of smokers.…”
Section: Discussionmentioning
confidence: 62%
“…All this highlights the need to act responsibly to fight this epidemic. However, how patients seek help is often not considered [1,2]. It is also important to highlight that the mechanisms that sustain and maintain obesity and overweight are not socially known.…”
Section: Introductionmentioning
confidence: 99%